Band of outsiders - Godard's,Jean-Luc (The Criterion Collection, 2003)
Two restless youngmen( Sami Frey & Claud Prassuer) enlist the object of their desire (Anna Kareena) to help them commit a robberry- in her own home.French new wave a pioneer Jean -Luc Godard takes to the streets of Paris to re-imagine the gangster genere,spinning an audicious yarn that's at once sentimental and insoucient,romantic and meloncholy.The criterion collection is proud to present the convention-flouting postmodern classic Band of outsiders.